Mid-term clinical follow-up of the Columbus® cruciate retaining total knee replacement. Issue 6 (November 2015) - Sciberras, Nadia C.; Deakin, Angela H.; Picard, Frederic
Abstract : Background: The navigated Columbus ® total knee arthroplasty (TKA) is a relatively new implant with few published mid-term follow-up reports. This retrospective study assessed the clinical and radiographic outcomes of a consecutive series of these implants. Methods: One hundred and seventy-eight knees in 165 patients were identified. The patient cohort had a mean age of 69 (50-89) years. Follow-up of 105 knees (59%) was 60.6 (58-76) months. All complications and readmissions within the cohort were identified via the Scottish Information Services Division (NHS Scotland). Survival analysis was carried out for all 178 knees using Kaplan-Meier, with hospital and national records used to identify the last known date when the patient was alive and the prosthesis was still in place. Results: Four patients had a revision TKA (all cause revision rate 2.2%) giving a cumulative 5-year survival of 97.3% (95% CIs 92.9%, 99.9%) with revision for any cause as the endpoint. Only one patient required revision for aseptic loosening. The mean maximal active flexion was 100.3 (60-120) degrees, with a mean fixed flexion of 0.4 (0-5) degrees. Ninety-six percent of the patients were either satisfied or very satisfied with their operation. The mean Oxford knee score was 37 (5-48), the median Knee Society Score was 86 (51-99), and median Knee Society function score was 90 (5-100). Conclusions: The results of this study are comparable to those reported in the National Joint Registry and show that the implant is functioning well at 5 yr.